Regional ambient temperature is associated with human personality - Wei, Wenqi; Lu, Jackson G.; Galinsky, Adam D.; Wu, Han; Gosling, Samuel D.; Rentfrow, Peter J.; Yuan, Wenjie; Zhang, Qi; Guo, Yongyu; Zhang, Ming; Gui, Wenjing; Guo, Xiao-Yi; et al. (Nature human behaviour, 2017)
Human personality traits differ across geographical regions 1 – 5 . However, it remains unclear what generates these geographical personality differences. Because humans constantly experience and react to ambient temperature, we propose that temperature is a crucial environmental factor that is associated with individuals’ habitual behavioural patterns and, therefore, with fundamental dimensions of personality. To test the relationship between ambient temperature and personality, we conducted two large-scale studies in two geographically large yet culturally distinct countries: China and the United States. Using data from 59 Chinese cities ( N = 5,587), multilevel analyses and machine learning analyses revealed that compared with individuals who grew up in regions with less clement temperatures, individuals who grew up in regions with more clement temperatures (that is, closer to 22 °C) scored higher on personality factors related to socialization and stability (agreeableness, conscientiousness, and emotional stability) and personal growth and plasticity (extraversion and openness to experience). These relationships between temperature clemency and personality factors were replicated in a larger dataset of 12,499 ZIP-code level locations (the lowest geographical level feasible) in the United States ( N = 1,660,638). Taken together, our findings provide a perspective on how and why personalities vary across geographical regions beyond past theories (subsistence style theory, selective migration theory and pathogen prevalence theory). As climate change continues across the world, we may also observe concomitant changes in human personality. Personality traits differ across geographical regions, suggesting a role for environmental factors. Wei, Lu, and colleagues show an association between regional ambient temperature and personality in two large studies conducted in China and the United States.